Czech and Slovak cinema [ theme and tradition - Hames, Peter (Edinburgh : Edinburgh University Press, 2009)
Examines the key themes and traditions of Czech and Slovak cinema, linking inter-war and post-war cinemas together with developments in the post-Communist period.
1.Introduction -- 2. History -- 3. Comedy -- 4. Realism -- 5. Politics -- 6. The Holocaust -- 7. Lyricism -- 8. The Absurd -- 9. The avant-garde -- 10. Surrealism -- 11. Animation -- 12. Slovak directions
Includes bibliographical references (p 229-253) and index
Keywords: Motion pictures -- Czech Republic -- History; Motion pictures -- Czech Republic -- Plots, themes, etc; Motion pictures -- Slovakia -- History; Motion picture -- Slovakia -- Plots, themes, etc; Motion pictures